Bio-Foam Kaliandra: A Portable Fire Extinguisher Innovation Based on Waste Cooking Oil for Household Fire Mitigation: Bio-Foam Kaliandra: Inovasi APAR Portabel Berbasis Minyak Jelantah untuk Mitigasi Kebakaran Rumah Tangga - Muhammad Akbar Syahputra (ANDIL Mulawarman Journal of Community Engagement, 2026)
Dense residential areas face a high risk of household fires due to limited access to firefighting services and the lack of early-stage fire suppression facilities at the household level. Meanwhile, waste cooking oil generated from households remains underutilized and poses potential environmental pollution. This study aims to develop an innovation framework for a portable fire extinguisher (APAR) based on bio-foam formulated from soap-based surfactants derived from waste cooking oil as an effort for early-stage fire mitigation. The method includes community-based fire mitigation education, formulation of Bio-Foam Kaliandra through a saponification process, small-scale fire extinguishing simulations, and evaluation based on community feedback. The results indicate that the produced bio-foam has the potential to serve as an alternative extinguishing medium by forming a stable foam layer that suppresses oxygen supply, reduces temperature, and decreases fire intensity. In addition, the evaluation results show an improvement in community understanding and a positive level of acceptance toward this innovation. The novelty of this study lies in integrating household waste management with community-based fire mitigation through a simple, applicable, and locally resource-based technology. This innovation not only provides an alternative early fire suppression tool but also adds value to waste cooking oil as a sustainable waste-to-product solution. Overall, Bio-Foam Kaliandra demonstrates strong potential to enhance community preparedness in responding to household fires and to support the development of sustainable and replicable community-based disaster mitigation programs.